Early targeted heart rate aerobic exercise versus placebo stretching for sport-related concussion in adolescents: a randomised controlled trial. (November 2021) - Leddy, John J; Master, Christina L; Mannix, Rebekah; Wiebe, Douglas J; Grady, Matthew F; Meehan, William P; Storey, Eileen P; Vernau, Brian T; Brown, Naomi J; Hunt, Danielle; Mohammed, Fairuz; Mallon, Andrea; et al.
Summary: Background: Sport-related concussion is a public health problem, particularly in adolescents. Quality of life is reduced in adolescents with persistent post-concussive symptoms (symptoms >28 days). We replicated a previous randomised controlled trial to validate the safety, efficacy, and generalisability of, and objective adherence to, prescribed early targeted heart rate subsymptom threshold aerobic exercise compared with placebo-like stretching exercise for adolescent recovery from sport-related concussion and for reducing the risk of persistent post-concussive symptoms. Methods: This randomised controlled trial was done at three community and hospital-affiliated sports medicine concussion centres in the USA. Male and female adolescent athletes (aged 13–18 years) presenting within 10 days of sport-related concussion were randomly assigned to individualised subsymptom threshold aerobic or stretching exercise at least 20 min daily, for up to 4 weeks after injury. Exercise adherence and intensity were measured by heart rate monitors. The primary outcome was clinical recovery (ie, return to baseline symptoms, normal exercise tolerance, and a normal physical examination) within the 4-week intervention period, and development of persistent post-concussive symptoms beyond 28 days after injury. This study is registered with ClinicalTrials.gov, NCT02959216 . Findings: Between Aug 1, 2018, and March 31, 2020, 118 adolescents were recruited (61 were randomly assigned to the aerobic exercise group and 57 to the stretching exercise group) and included in the intention-to-treat analysis. On survival analysis, controlling for sex, site, and mean daily exercise time, patients assigned to aerobic exercise were more likely to recover within 4 weeks after injury compared with those assigned to stretching exercise, with a 48% reduced risk of persistent post-concussive symptoms (hazard ratio for stretching vs aerobic exercise of 0·52 [95% CI 0·28–0·97], p=0·039). No adverse events were reported. Interpretation: This multicentre study found that early treatment with subsymptom threshold aerobic exercise safely speeds recovery from sport-related concussion and reduces the risk for persistent post-concussive symptoms, an important result given the impact of delayed recovery on adolescent quality of life. Adherence was good and there were no adverse events from this non-pharmacological treatment. These results suggest that physicians should not only permit, but consider prescribing, early subsymptom threshold physical activity to adolescents as treatment for sport-related concussion and to reduce the risk of persistent post-concussive symptoms. Funding: American Medical Society for Sports Medicine.